Effects of temper annealing temperatures and times on the mechanical properties of cold-worked aluminium 1200 (1989)
Experiments have been conducted to develop temper- annealing schedule for continusly cast and cold-worked aluminium 1200. By using the method of graphical combination of the results of tensile and deep- drawn test, it is shown that a cost-effective temper-annealing schedule that would impart improved mechanical properties( compared with full annealing at 460° C for 6 hours) can be developed for Al-1200. For optimum combination of desired properties during deep- drawing, the 75% cold-worked material should be temper-annealed at 380 °C for 3 hours; the 85% cold-worked material should be temper-annealed at 400 C for 2 hours while the 90% cold-worked Al-1200 should be temper-annealed at 460 °C for 3 hours